Use of RAPD and PCR double amplification in the study of ancient DNA - F. Balzano; E. Mura; A. Mura; G. Lepore; M. Zedda (Journal of Biological Research, 2011)
This project analysed the DNA extracted from bones of ancient sheep which have been brought to light in Sardinian different archaeological sites. In order to better analyse this highly fragmented DNA, a double amplification technique was chosen. The first approach consisted of RAPD-PCR abd the second one in classic PCR. The RAPD-PCR amplified random fragments and allowed the production of numerous amplicons. The products of RAPD amplification have been amplified, more specifically, by the second PCR using primers for a sequence of 176 bp of mitochondrial D-loop region. These DNA fragments have been sequenced and the sequence analysis has confirmed that it belonged to Ovis aries. Consequently, this provedure can be considered a valid tool to perform amplification of degraded DNA, such as ancient DNA.